Clinical outcomes in patients who discontinue natalizumab therapy after 2 years in the Tysabri® Observational Program (TOP). (March 2021) - Butzkueven, Helmut; Trojano, Maria; Kappos, Ludwig; Spelman, Tim; Wiendl, Heinz; Rosales, Karen; Su, Ray; Licata, Stephanie; Ho, Pei-Ran; Campbell, Nolan
Background: Natalizumab is a highly efficacious therapy for relapsing–remitting multiple sclerosis (RRMS). Patients who discontinue natalizumab may experience return of MS disease activity. Objective: The aim of this study was to analyze predictors of post-natalizumab disease activity return. Methods: The Tysabri ® Observational Program (TOP) is an ongoing observational study of natalizumab-treated RRMS patients. Patients discontinuing natalizumab are encouraged to remain in TOP. Results: Analyses included 3221 TOP patients. After ⩾2 years on natalizumab, relapse risk was twice as high for patients who switched to an oral therapy ( n = 660, hazard ratio (HR) = 2.18, p < 0.001) and three times as high for patients who switched to an injectable therapy ( n = 95, HR = 3.02, p < 0.001) as for those who stayed on natalizumab ( n = 2466). Relapse rates after switching remained below pre-natalizumab rates. In patients who switched to an oral therapy, higher relapse risk was predicted by longer washout time, more pre-natalizumab relapses, higher Expanded Disability Status Scale score at natalizumab initiation, and shorter natalizumab treatment duration. Conclusion: Patients who stayed on natalizumab had better clinical outcomes than those who switched to an oral or injectable therapy after ⩾2 years on natalizumab. These results highlight modifiable risk factors for disease activity return (e.g. natalizumab treatment duration and washout duration) to consider when making treatment decisions.